Mutations in Hsp90 Cochaperones Result in a Wide Variety of Human Disorders - Johnson, Jill L. (Frontiers in Molecular Biosciences, 2021)
The Hsp90 molecular chaperone, along with a set of approximately 50 cochaperones, mediates the folding and activation of hundreds of cellular proteins in an ATP-dependent cycle. Cochaperones differ in how they interact with Hsp90 and their ability to modulate ATPase activity of Hsp90. Cochaperones often compete for the same binding site on Hsp90, and changes in levels of cochaperone expression that occur during neurodegeneration, cancer, or aging may result in altered Hsp90-cochaperone complexes and client activity. This review summarizes information about mutations within the protein coding sequence of cochaperones that have been linked to disease. Cochaperone mutations result in ciliary or muscle defects, neurological development or degeneration disorders, and other disorders. In many cases, diseases were linked to defects in established cochaperone-client interactions. A better understanding of the functional consequences of defective cochaperones will provide new insights into their functions and to may lead to specialized approaches to modulate Hsp90 functions and treat some of these human disorders.